Income, Employment and Health Risks of Older Workers - Wei, Siqi (Centro de Estudios Monetarios y Financieros, 2022)
This paper begins with the observation that many olderworkers move to "bridge" jobs with lower wages and fewer working hours before exiting the labor force for good. To explain this gradual transition to full retirement, I propose a nonlinear agingrelated shock — mismatch shock, which mismatches workers with their existing job and triggers job leaves. I develop an empirical framework of employment and job transitions jointly with stochastic wage and hour processes to separate health risks, individual-specific productivity risks, firm-specific mismatch risks, quality of outside offers, and job destruction risks faced by older workers. The model is estimated with a sample of male individuals aged 51 to 70 in the US Health and Retirement Study applying a novel parameter-expanded stochastic EM algorithm. The paper finds that mismatch shocks play an important role in explaining the reduction in wages and hours for movers. Furthermore, I calculate the welfare cost of risks and quantify how much individuals value the possibility of a flexible transition to full retirement by constructing a utility-based structural model of consumption, employment and job movements where agents face the same risks as in the empirical model. The model is estimated using a novel simulation-based algorithm that exploits the connection to the empirical model and the estimates from the empirical model. The results show that the median cost of mismatch risks amounts to a reduction in consumption flow by 5?3%-7?1% depending on the education group. Banning job changes and re-entry causes a welfare loss equivalent to a consumption drop of 12% 4%.
Keywords: Income risks; Health risks; Mismatch; Bridge jobs; Latent variables.